Deaths of Detainees and Convicted Prisoners in Konya Provincial and District Prisons - Demirci, Şerafettin; Doğan, Kamil Hakan; Erkol, Zerrin; Deniz, İdris; Günaydın, Gürsel (The Bulletin of Legal Medicine, 2008)
If anybody dies in prison or under police protection, the case should be investigated carefully in order to define, with no suspicion, the death of people who are delivered to government and in government responsibility; it is also necessary to disclose whether there is lameness in government responsibility or not. In this paper, cases of detainees and convicted prisoners who died in Konya provincial and district prisons between 2001 and 2007 and on whom autopsies were performed were evaluated in respect of their demographic features, crimes for which they were imprisoned, location of death, duration of their stay in prison, manner of death and cause of death. For this purpose, autopsy reports of Konya Branch of Forensic Medicine Council between 2001 and 2007 were investigated retrospectively. Ages of 32 detainees and convicted prisoners' death cases, all of whom were male, varied between 25 and 81 and average age was found to be 44.5 + 15.1 years. Among reasons for their imprisonment, it was found that "premeditated murder" was the most seen reason with 11 cases (34.4%). Deaths occurred in prison in 12 cases (37.5%) and in hospital in 20 cases (62.5%). The duration of the cases' stay in prison before their death varied between 1 day and 5 years and average duration was 2.26 years. It was determined that death occurred due to natural causes in 25 cases (78.1%) and among the natural deaths, infections were the first with 9 cases (36%). The present article points out that if a serious disease that requires treatment is detected through periodical examinations conducted at entry to prison and later in detainees and convicted prisoners who were imprisoned on account of a crime/crime allegation, it would be more appropriate to send them to hospital rather than prison.Key words: Convicted prisoner, detainee, prison, death
Keywords: convicted prisoner; detainee; prison; death